INCREASED LIFE SKILL ADOLESCENT ORPHANAGE THROUGH THE DIVERSIFICATION OF OIL CITRONELLA AS A BIOPESTICIDE - warsito warsito warsito (Journal of Innovation and Applied Technology, 2017)
Some essential oils have been shown to have activity as a natural pesticide that is effective and safe for humans and the environment. This activity aims to enhance the skills of adolescent Al Kaaf’s orphanage through diversification of citronella oil into products biopesticides. Diversification citronella oil into a biopesticide made through three main activities, namely (1) briefing on biopesticides and knowledge-based biopesticide formulations ways citronella oil, (2) packaging and labeling of products biopesticides and (3) test the activity against H. armigera insect. The results of these activities have improved insight on biopesticides, inspire and enhance creativity and life skills for adolescents are cared for Al Kaaf’s orphanage. Formula of biopesticide that is composed of citronella oil and clove oil (ratio 1: 1) has the power to kill insect pests of H. armigera faster than formula biopesticide consisting of citronella oil and basil oil (ratio 1: 1). The test results also show formula-based biopesticides this essential oil is a contact poison against H. armigera insect pests.